2005
DOI: 10.1212/01.wnl.0000183148.34197.2e
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of fatty fish on dementia risk are stronger for those without APOE ε4

Abstract: In the Cardiovascular Health Cognition Study, consumption of fatty fish was associated with a reduced risk of dementia and Alzheimer disease for those without the APOE epsilon4 allele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
175
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(188 citation statements)
references
References 28 publications
10
175
1
2
Order By: Relevance
“…A number of studies investigated the relation of fish intake to risk of developing AD. In all cases, the estimated OR were in the protective direction and most were statistically significant at a low level of intake of just one fish meal per week (133)(134)(135)(136)(137)(138)144) . The Rotterdam Study reported significant reduction in risk after 2 .…”
Section: Cardiovascular Mechanisms Of Fish Protectionmentioning
confidence: 91%
See 1 more Smart Citation
“…A number of studies investigated the relation of fish intake to risk of developing AD. In all cases, the estimated OR were in the protective direction and most were statistically significant at a low level of intake of just one fish meal per week (133)(134)(135)(136)(137)(138)144) . The Rotterdam Study reported significant reduction in risk after 2 .…”
Section: Cardiovascular Mechanisms Of Fish Protectionmentioning
confidence: 91%
“…In prospective studies, consumption of fish was associated with lower risk of incident dementia (133)(134)(135)(136)(137)(138) , stroke (139,140,141,142) , and cognitive decline (86,143) . A number of studies investigated the relation of fish intake to risk of developing AD.…”
Section: Cardiovascular Mechanisms Of Fish Protectionmentioning
confidence: 99%
“…10 Paradoxically, the negative association between high-fat diets and AD is predominantly limited to E4 non-carriers in some studies. 102,103 We recently published work showing that in older adults, E4 carriers actually showed cognitive improvements on some tasks after ingesting a high-fat meal, compared to a high carbohydrate meal. 72 We speculate that because of the lipid deficit in the E4 carrier brain, high fat feeding may benefit E4 carriers acutely.…”
Section: Triglycerides Cognition and Apoe Statusmentioning
confidence: 99%
“…Table 1 summarizes the few epidemiological studies that have tested and evidenced this interaction. The first two studies (Barberger- Gateau et al, 2007;Huang et al, 2005) have examined the association between fish consumption and incidence of dementia. Both have found that the risk of dementia was decreased by 40% by regular fish consumption only in APOE4 non-carriers while no association was observed in APOE4 carriers.…”
Section: Interactions Between Lc N-pufa and Apoe4 On Cognitionmentioning
confidence: 99%